Dimethyl-2-oxoglutarate improves redox balance and mitochondrial function in muscle pericytes of individuals with diabetes mellitus - Faulkner, A; Tamiato, A; Cathery, W; Rampin, A; Caravaggi, CM; Jover, E; Allen, S; Mellor, H; Hauton, D; Heather, LC; Spinetti, G; Madeddu, P (Springer, 2020)
Aims/hypothesis Treatment of vascular complications of diabetes remains inadequate. We reported that muscle pericytes (MPs) from limb muscles of vascular patients with diabetes mellitus display elevated levels of oxidative stress causing a dysfunctional phenotype. Here, we investigated whether treatment with dimethyl-2-oxoglutarate (DM-2OG), a tricarboxylic acid cycle metabolite with antioxidant properties, can restore a healthy metabolic and functional phenotype.